2022
DOI: 10.1021/acs.macromol.2c00920
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Photothermal Synthesis of Polyurethane from Blocked Isocyanates

Abstract: Though it has been shown that the photothermal heating by pulsed lasers can provide localized heat to cure polymers at an enhanced rate without bulk temperature changes, such an approach has been unsuccessful at driving chemical transformations that require large increases in bulk temperature�such as the curing of blocked isocyanates. We show that photothermal heating using 1 W of continuous wave laser power directed toward a mixture of 6 wt % carbon black in a blocked isocyanate is sufficient to reach tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…For the pure alcohols, the polyol is roughly an order of magnitude more viscous than butanediol, while the butanediol is an order of magnitude more viscous than butanol. The first system (HDI + K-Flex 188) has been used in our prior research 24 and produces a linear polymer that forms a solid at high conversions. Moving to butanediol allows us to reduce the viscosity of the initial reactive mixture while still producing a linear polymer that will form a solid at high conversions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the pure alcohols, the polyol is roughly an order of magnitude more viscous than butanediol, while the butanediol is an order of magnitude more viscous than butanol. The first system (HDI + K-Flex 188) has been used in our prior research 24 and produces a linear polymer that forms a solid at high conversions. Moving to butanediol allows us to reduce the viscosity of the initial reactive mixture while still producing a linear polymer that will form a solid at high conversions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We chose to examine the influence of these parameters using the reaction between alcohol and isocyanate groups to form urethanes, driven by the photothermal effect of gold nanoparticles (AuNPs). Our group has shown that this approach is effective for generating cross-linked polymers from viscous prepolymers, but has not yet sought to extend this to low-viscosity systems or those that do not generate polymers. Additionally, our early work on urethane formation , focused on using high-powered pulsed lasers in order to attain the highest local temperatures we could, while more recent work has shown that CW lasers can also be effective .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that photothermal catalysis could merge the advantages of photocatalysis -the temporal and spatial control over radical formation -with the generality of heat. [13][14][15][16][17][18] Fig. 1: Employing photothermal catalysis for chemical recycling to monomer.…”
mentioning
confidence: 99%